Review Paper on Text mining and Sentimental analysis (International Journal of Engineering and Computer Science, 2017)
In this paper we discussed about most emerging field of computer science engineering name as Big Data. This paper provides you detailed information about big data from basic to advance level. In this paper we presented detailed review of the sentimental analysis and text analysis which will provide you deep insight of the work done in this and provides outline about the scope in this area and motivate research work in this and apply it on the real life application. It is solitary of the majority vigorous research areas in natural language processing and text mining in latest years. Its attractiveness is primarily due to two reasons. Due to extensive assortment of applications because opinions are innermost to approximately all human activities and are key influencers of our behaviors. Whenever we necessitate making a pronouncement, we want to hear others‟ opinions it presents many challenging research problems, which had never been attempted before the year 2000. Part of the reason for the lack of study before was that there was little opinionated text in digital forms